Pediatric and adult osteoporosis: a contrasting mirror - Hanene Lassoued Ferjani; Ines Cherif; Dorra Ben Nessib; Dhia Kaffel; Kaouther Maatallah; Wafa Hamdi (Korean Society of Pediatric Endocrinology, 2024)
Pediatric osteoporosis (PO) is a condition that is currently gaining recognition. Due to the lack of official definitions over the past few decades, the exact incidence of PO is unknown. The research does not provide a specific prevalence of PO in different world regions. However, this is expected to change with the latest 2019 guidelines proposed by the International Society of Clinical Densitometry. Although adult osteoporosis (AO) has been postulated a pediatric disease because its manifestation in adulthood is a result of the bone mass acquired during childhood, differences between PO and AO should be acknowledged. AO is defined as low bone density; however, PO is diagnosed based on existing evidence of bone fragility (vertebral fractures, pathological fractures). This is particularly relevant because unlike in adults, evidence is lacking regarding the association between low bone density and fracture risk in children. The enhanced capacity of pediatric bone for reshaping and remodeling after fracture is another difference between the two entities. This contrast has therapeutic implications because medication-free bone reconstitution is possible under certain conditions; thus, background therapy is not always recommended. In this narrative review, differences between PO and AO in definition, assessment, and medical approach were investigated.